Hubungan Terpaan Iklan dan Kredibilitas Brand Ambassador Dengan Minat Beli Produk Vivo Smartphone. - Bianca Nuriena Nisa; Sri Widowati Herieningsih (Interaksi Online, 2020)
This research aims to determine the effect of Vivo’s Smartphone advertising exposure and the credibility of brand ambassador on the interest in purchasing intentions of Vivo Smartphone Theories used are Strong Theory of Communication and concept from Schiffman & Kanuk and Hani et. Al. The sampling technique used is nonprobability sampling, conducted by purposive sampling with a sample of 60 people with the criteria as follow; men and women aged 22-30 years who lived in Semarang, had watched Vivo V17 Pro advertisement, have never bought Vivo Smartphone and recognize the brand ambassador of Vivo. Survey are carried out using the Kendall’s Tau B analysis. The results showed that the significance value for the Vivo advertising exposure variable and variable credibility of brand ambassador were 0,430 and 0,108 which means had no significance.